Empowering Educators: Website Media Training for Japanese Language Teachers in Malang Raya - Sutiyarti, Ulfah; Dewandono, Wiranto Aji; Saragih, Febi Ariani (Jurnal Gramaswara: Jurnal Pengabdian kepada Masyarakat, 2024)
Websites can serve as effective learning media, especially in the Covid-19 era that necessitates distance learning. The potential for developing educational websites is vast, given the increasingly dynamic and mobile society and the diverse educational needs. This learning concept is expected to create an effective and innovative learning atmosphere, motivating both students and teachers. Based on this background, there is a need for activities that contribute to the development of Japanese language learning in Indonesia, particularly for Japanese language teachers in Malang Raya through Malang MGMP. To address this, the Japanese Language Education Study Program, Faculty of Cultural Sciences, Universitas Brawijaya, organized a training themed “Training on Making Mobile Learning Media as a Means of Increasing Skills for Making Japanese Learning Media for MGMP Teachers of Malang Raya.” This training aims to make Japanese language learning more interesting, innovative, and accessible from anywhere. Keywords: website media; japanese language learning; training